Perspectives on environmental problems - Glasbergen, P.; Blowers, Andrew (London : Arnold ; New York : Halsted Press, 1995)
The three volumes of Environmental Policy in an International Context have been developed by the Dutch and UK Open Universities as part of the International Environmental Series. They accompany a workbook and six videos. The first volume takes a critical and analytical look at contemporary environmental issues built around the key questions - what are international and environmental problems; and why have they become important politically? These questions are examined from a variety of viewpoints - science, sociology, politics, law and economics. A multi-disciplinary approach is emphasised and it shows how both technical and scientific solutions need to be sought alongside.
Environmental problems in an international context * Science on environmental problems * The social construction of environmental problems * Environmental problems in their political context * Principles of international environmental law * Environmental problems from an economic perspective * The search for sustainable development * Bibliography * Index * Author's biography.
Περιέχει βιβλιογραφία και ευρετήριο.
Keywords: Environmental policy -- International cooperation; Environmental policy -- Political aspects; Electronic books